2009
DOI: 10.1177/0022034509347168
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Post-orthodontic Lesions by a Remineralizing Cream

Abstract: Orthodontic patients have an increased risk of white-spot lesion formation. A clinical trial was conducted to test whether, in a post-orthodontic population using fluoride toothpastes and receiving supervised fluoride mouthrinses, more lesions would regress in participants using a remineralizing cream containing casein phosphopeptide- amorphous calcium phosphate compared with a placebo. Forty-five participants (aged 12-18 yrs) with 408 white-spot lesions were recruited, with 23 participants randomized to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
2
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(236 citation statements)
references
References 30 publications
7
218
2
9
Order By: Relevance
“…In one of the first clinical trials of CPP-ACP cream used specifically for treatment of postorthodontic WSLs, Bailey et al [46] reported that use of CPP-ACP cream enhanced the regression of WSLs compared with a placebo. However, more recent clinical investigations show less promising results.…”
Section: After the Orthodontic Treatmentmentioning
confidence: 99%
“…In one of the first clinical trials of CPP-ACP cream used specifically for treatment of postorthodontic WSLs, Bailey et al [46] reported that use of CPP-ACP cream enhanced the regression of WSLs compared with a placebo. However, more recent clinical investigations show less promising results.…”
Section: After the Orthodontic Treatmentmentioning
confidence: 99%
“…The greater decrease in DD readings for lesions in test group compared to control may be taken to indicate a larger reversal of the early caries process due to the repeated CPP-ACP application. Several methods had been used for screening WSLs after orthodontic treatment such as QLF, DIAGNOdent or clinical scores [11][12][13][14][15][16] . On the other hand the DIAGNOdent readings should be interpreted with caution because statistically significant differences might not necessarily have clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…We used ICDAS II for activity evaluation of free smooth surfaces in this study. Clinical investigation were taken into consideration for detecting enamel lesion activity were based on a modification of the Bailey et al caries lesion activity assessment criteria and implicate visual appearance, tactile sensation and potential for plaque accumulation 15) . The Gorelick Index to screen WSL is so far the most utilized procedure to record WSL in orthodontic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this trial, conducted by authors significant improvements were noted in both groups, but the number of white spot lesions that had completely disappeared after 12 months was significantly greater in the CPP-ACP group (63% versus 25%, respectively; p<0.05). 27 Remineralization potential of CPP-ACP paste has been confirmed by many another clinical trial by Bailey DL et al, 28 Iijima et al, 29 Reynolds et al, 22 Akin M et al 30 Mechanism behind this is that CPP-ACP has been shown to localize and stabilize calcium and phosphate ions at the tooth surface in a bioavailable form that can promote remineralization of enamel subsurface lesions in situ, restoring the white opaque appearance of the lesions to translucency.…”
mentioning
confidence: 93%